1970
DOI: 10.1113/jphysiol.1970.sp009269
|View full text |Cite
|
Sign up to set email alerts
|

The glycogenolytic response to stimulation of the splanchnic nerves in adrenalectomized calves

Abstract: SUMMARY1. The effects of stimulation of the peripheral ends of one or both splanchnic nerves have been investigated in adrenalectomized calves at different ages.2. During the first 24 hr after birth unilateral splanchnic nerve stimulation led to a prompt rise in the plasma glucose concentration and this response was more than doubled when both nerves were stimulated simultaneously. Under these latter conditions hyperglycaemia was found to be associated with a measurable loss of glycogen from the liver.3. Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

1971
1971
2015
2015

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 22 publications
0
40
0
1
Order By: Relevance
“…Several studies showed that plasma glucose concentrations increased immediately after birth, without nutrient intake [68,101]. The rise of glucose concentration in the blood is a result of postnatal glycogenolysis that is associated with an increase in sympathetic efferent activity [102]. Sympathetic activity at birth also increases by as much as six fold, and the plasma free fatty acid concentration in the lamb rises within 2 h of birth [103].…”
Section: Carbohydrate Metabolism and Energy Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies showed that plasma glucose concentrations increased immediately after birth, without nutrient intake [68,101]. The rise of glucose concentration in the blood is a result of postnatal glycogenolysis that is associated with an increase in sympathetic efferent activity [102]. Sympathetic activity at birth also increases by as much as six fold, and the plasma free fatty acid concentration in the lamb rises within 2 h of birth [103].…”
Section: Carbohydrate Metabolism and Energy Homeostasismentioning
confidence: 99%
“…Glycogen stores are rapidly mobilized and broken down in the starved calf [102]. Glucose is used for thermogenesis and for physical activity.…”
Section: Brown Adipose Tissue Metabolism and Thermogenesismentioning
confidence: 99%
“…Niijima (16) demonstrated that intravenous injection of glucose increased the efferent ®ring rate in the hepatic branch of the vagus nerve in rats, and that the ®ring rate was directly related to the arterial blood glucose concentration over a range of physiologic concentrations (3.3±25.0 mmol/l). On the other hand, sympathetic stimulation was shown to activate glycogen phosphorylase and glucose-6-phosphatase (G-6-Pase) in rabbits (17) and to deplete hepatic glycogen reserves and increase net hepatic glucose output in calves (18). In 18 h fasted conscious dogs, infusion of somatostatin, 4-fold basal insulin, basal glucagon, and glucose to increase arterial glucose concentrations to 9±11 mmol/l was associated with a 38% reduction in hepatic norepinephrine spillover (19).…”
Section: Autoregulation In Response To Hyperglycemiamentioning
confidence: 99%
“…Thus, although experiments in which the peripheral ends of both splanchnic nerves are stimulated maximally for prolonged periods serve to demonstrate the occurrence of glycogenolysis in the liver in response to sympathetic stimulation in adrenalectomized animals, they do not necessarily provide a useful indication of the sensitivity of the underlying mechanism. The hyperglycaemic response to stimulation of the peripheral ends of either the left or the right splanchnic nerve has therefore been examined in greater detail in the adult cat and dog since the response in the calf had been shown to change with age during the first few weeks after birth (Edwards & Silver, 1970).…”
Section: Responses To Stimulation Of Both Splanchnic Nervesmentioning
confidence: 99%